Makna Metafisika Kebersamaan Gabriel Marcel dan Hubungannya dengan Kerukunan Umat Beragama di Indonesia - Wulan Kusuma Wardani; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This research uses a qualitative approach that comes from several journals and books. This study aims to discuss the relationship between Gabriel Marcel's metaphysics of togetherness and inter-religious harmony in Indonesia. The results and discussion of this study are that positioning other people as subjects creates intersubjectivity relations. This relationship implies the creation of a union relationship. A meaningful union understands each other, respects each other, and is able to bring a person to his fullness. The relation of intersubjectivity also implies the fusion of I-you to become us. This fusion brings a sense of unity and a willingness to live side by side between adherents of different religions. This study concludes that Marcel's Metaphysics of togetherness changes the relationship that was originally subject-object to becoming subject-subject. This subject-subject relation, in Marcel's terms, is also known as the I-you relation. This relationship creates a sense of unity. Unity which means mutual understanding, mutual respect. The sense of unity also forms the will to live side by side between adherents of different religions.